2022
DOI: 10.33737/gpps21-tc-96
|View full text |Cite
|
Sign up to set email alerts
|

Effects of impeller blades with bow trailing edge on centrifugal compressor performance

Abstract: The performance of centrifugal compressors can be improved by reducing the reverse flow intensity of their impellers’ outlet. This study used numerical simulations to investigate the effects of applying bow trailing edge to the impeller blades on the performance of a centrifugal compressor with a wedge diffuser. A peak efficiency 0.87% higher than that of the baseline centrifugal compressor is gained by using positive bow trailing edge on impeller blades. Flow in both the impeller and the diffuser is improved.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In addition, for the impeller trailing edge at the radial outlet, Hildebrandt et al [22] indicated that the trailing edge backward sweep makes the outlet velocity and flow angle distribution more uniform, which was beneficial in the diffuser inside flow. Li et al [23] analyzed the influence of impeller trailing edge sweep and found that backward sweep can improve flow conditions near the trailing edge, but it can cause non-uniform pressure distribution at the outlet and increase downstream losses in the diffuser. Tian et al [24] studied two types of swept impeller at the trailing edge, incline swept and free swept.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for the impeller trailing edge at the radial outlet, Hildebrandt et al [22] indicated that the trailing edge backward sweep makes the outlet velocity and flow angle distribution more uniform, which was beneficial in the diffuser inside flow. Li et al [23] analyzed the influence of impeller trailing edge sweep and found that backward sweep can improve flow conditions near the trailing edge, but it can cause non-uniform pressure distribution at the outlet and increase downstream losses in the diffuser. Tian et al [24] studied two types of swept impeller at the trailing edge, incline swept and free swept.…”
Section: Introductionmentioning
confidence: 99%